PENYULUHAN TENTANG MANFAAT DAUN GAMBIR (Uncaria gambir (Hunter) Roxb.) SEBAGAI OBAT KUMUR DI DESA PATUMBAK - Zola Efa Harnis; Bunga Rimta Barus; Palas Tarigan (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Gambir is a latex juice extracted from the leaves of the gambier plant (UncariagambirRoxb) by pressing. Gambir contains two main components, namely catechins and catechutannic acid, which has many benefits. Gambir has astringent, antibacterial, and other pharmacological and toxic properties. Gambir in Indonesia is generally used for betel nut, besides that it is also used to treat canker sores and mouthwash for sore throats. This counseling aims to obtain data on counseling about the benefits of gambir leaves as mouthwash in Patumbak Village. Counseling was carried out using an interactive method between the presenters and participants so that the event took place in an interesting manner and provided education to the community about the benefits of gambir leaves as mouthwash in Patumbak Village. The results obtained from this counseling are lack of understanding or lack of knowledge of the community following counseling in Patumbak Village about the benefits of gambir leaves as mouthwash, by providing guidance and assistance with counseling methods, the results obtained where the community, especially those who participated in the counseling, showed enthusiasm in their curiosity about the benefits of the leaves. gambier as a mouthwash as well as increasing experience and knowledge of the people of Patumbak Village who participated together in counseling the benefits of gambir leaves as mouthwash through materials and simulations obtained during socialization. The conclusion of this counseling is that the community has been able to find out the benefits of gambier leaves that can be used as mouthwash.